2007
DOI: 10.1016/j.ijgo.2007.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Placental tissue iodine level and blood magnesium concentration in pre‐eclamptic and normal pregnancy

Abstract: Magnesium assimilation is known to be defective when iodine levels are insufficient. In northeast Anatolia, where iodine deficiency is common, clinical trials of iodine supplementation should be considered for pre-eclamptic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…This is consistent with previous studies that report a 45 mg/l UIC in pregnant women with preeclampsia (15,17). This data confirming that iodine deficiency is associated with hypertensive disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies that report a 45 mg/l UIC in pregnant women with preeclampsia (15,17). This data confirming that iodine deficiency is associated with hypertensive disease.…”
Section: Discussionsupporting
confidence: 93%
“…One of its main functions is the synthesis of thyroid hormones involved in the proper development of the fetus as well as in the regulation of various metabolic processes in adulthood. During gestation, iodine deficiency is a risk factor of preeclampsia (13)(14)(15)(16)(17). Iodine per se has several functions: bactericidal, apoptosis inducer, antioxidant, and it has been recently involved in migration, invasion and trophoblast differentiation (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of placental tissue samples have demonstrated that placenta contains iodine (4,5,6), and in vitro cell culture studies have suggested a functional role of NIS (10,11) and SMVT (19) in placental iodide transport. In addition, the chloride-iodide transporter pendrin has been proposed to play a role (11).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Placenta contains iodine (4,5,6) and evidence suggests that a number of iodide transporters are involved in placental iodide transport. Placental tissue and cell culture studies have demonstrated that the sodium iodide symporter (NIS) is expressed in different types of placental cells (7,8,9) and a functional role of NIS in placental iodide transport has been proposed (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…This ligand has been reported as iodine mediator [12,13,15,16,20,21]. Adequate iodine supplement is important for normal pregnancy, as iodine deficiency has been associated with oxidative stress and pregnant complications such as preeclampsia [22][23][24]. Iodine deprivation may activate the HIF-1α pathway or induce oxidative stress and impair bioenergetic homeostasis, leading to the perturbation of trophoblastic cell function and the placental vascular network.…”
Section: Introductionmentioning
confidence: 99%